2019
DOI: 10.3390/toxins11050282
|View full text |Cite
|
Sign up to set email alerts
|

Yellow Mealworm Larvae (Tenebrio molitor) Fed Mycotoxin-Contaminated Wheat—A Possible Safe, Sustainable Protein Source for Animal Feed?

Abstract: The aim of this study was to determine the potential for accumulation of deoxynivalenol (DON) in yellow mealworm larvae (Tenebrio molitor) reared on high DON Fusarium-infected wheat and investigate the effects on production, survival and nutritional traits. Wheat containing 200 μg/kg DON was used as the control diet. A different source of wheat was sorted into six fractions and mixed to obtain low (2000 μg/kg), medium (10,000 μg/kg) and high (12,000 μg/kg) levels of DON. Each diet was replicated five times wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 27 publications
1
43
1
Order By: Relevance
“…Recent studies have shown that insects — if kept on rotten and/or mouldy substrates—may render hazardous metabolites harmless via their own metabolism or largely excrete them, especially mycotoxins, such as zearalenone or type B trichothecenes (Niermans et al 2019 ; Ochoa Sanabria et al 2019 ; Van Broekhoven et al 2017 ). However, as shown for zearalenone, metabolism in T. molitor may also result in the formation of compounds of higher toxicity, such as α-zearalenol (Niermans et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that insects — if kept on rotten and/or mouldy substrates—may render hazardous metabolites harmless via their own metabolism or largely excrete them, especially mycotoxins, such as zearalenone or type B trichothecenes (Niermans et al 2019 ; Ochoa Sanabria et al 2019 ; Van Broekhoven et al 2017 ). However, as shown for zearalenone, metabolism in T. molitor may also result in the formation of compounds of higher toxicity, such as α-zearalenol (Niermans et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…It naturally occurs under the decaying bark of deciduous trees, as well as in tree hollows. It is a species which is bred as food for arthropods and cold‐blooded vertebrates . As a harmful species, it feeds in warehouses where flour, bran, rusks and other cereal products are stored.…”
Section: Introductionmentioning
confidence: 99%
“…The black soldier fly has shown to be able to degrade pathogens (Erickson et al 2004), mycotoxins (Purschke et al 2017), insecticides (Purschke et al 2017), and fungicides (Lalander et al 2016). Also, the yellow mealworm, when wheat was contaminated with the mycotoxin deoxynivalenol, accumulated only very low levels of the mycotoxin, suggesting that it can still be used to produce a sustainable, safe protein source (Sanabria et al 2019).…”
Section: Food Safety and Legislationmentioning
confidence: 99%